A Novel Complementation Assay for Quick and Specific Screen of Genes Encoding Glycerol-3-Phosphate Acyltransferases - Lei, Jie; Miao, Yingchun; Lan, Yu; Han, Xiuxiu; Liu, Hongbo; Gan, Yi; Niu, Leilei; Wang, Yanyan; Zheng, Zhifu (Frontiers in Plant Science, 2018)
The initial step in glycerolipid biosynthesis, especially in diverse allopolyploid crop species, is poorly understood, mainly due to the lack of an effective and convenient method for functional characterization of genes encoding glycerol-3-phosphate acyltransferases (GPATs) catalyzing this reaction. Here we present a novel complementation assay for quick and specific characterization of GPAT-encoding genes. Its key design involves rational construction of yeast conditional lethal gat1∆gat2∆ double mutant bearing the heterologous Arabidopsis AtGPAT1 gene whose leaky expression under repressed conditions does not support any non-specific growth, thereby circumventing the false positive problem encountered with the system based on the gat1∆gat2∆ mutant harboring the native episomal GAT1 gene whose leaky expression appears to be sufficient for generating enough GPAT activities for the non-specific restoration of the mutant growth. A complementation assay developed based on this novel mutant enables quick phenotypic screen of GPAT sequences. A high degree of specificity of our assay was exemplified by its ability to differentiate effectively GPAT-encoding genes from those of other fatty acyltransferases and lipid-related sequences. Using this assay, we show that Arabidopsis AtGPAT1, AtGPAT5 and AtGPAT7 can complement the phosphatidate biosynthetic defect in the double mutants. Collectively, our assay provides a powerful tool for rapid screening, validation and optimization of GPAT sequences, aiding future engineering of the initial step of the triacylglycerol biosynthesis in oilseeds.